The Importance of Improving Physical Fitness in Elementary School Children Through Sports and Physical Activities in Grade IV at SD Alwasiyah 10 Medan - Nur Habibah, Nur Habibah; Eti Hanifah Tamba; Afni Ajum Pulungan; Suyono (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Improving physical fitness is very important for elementary school children because it is related to their physical health, concentration in learning, and physical development. This study aims to determine how structured sports and physical activities can help improve the physical fitness of fourth grade students at SD Alwasiyah 10 Medan. The method used is a routine sports activity approach such as morning exercise, small ball games, and other physical activities that are interesting for children. The results show that students who are physically active have better endurance, more ideal body posture, and increased concentration in learning. This study emphasizes the importance of sports as part of school activities to form a healthy and active generation.